Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.4 - Multiplying Polynomials - Exercise Set - Page 289: 87



Work Step by Step

Replacing $x$ with $b-2$ in the given function, $ f(x)=x^2-3x $, then $f(b-2)$ is equal to \begin{array}{l} (b-2)^2-3(b-2) \\\\= (b)^2+2(b)(-2)+(-2)^2-3b+6 \\\\= b^2-4b+4-3b+6 \\\\= b^2+(-4b-3b)+(4+6) \\\\= b^2-7b+10 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.